2022
DOI: 10.3390/jof8020102
|View full text |Cite
|
Sign up to set email alerts
|

Application of Non-Thermal Plasma to Fungal Resources

Abstract: In addition to being key pathogens in plants, animals, and humans, fungi are also valuable resources in agriculture, food, medicine, industry, and the environment. The elimination of pathogenic fungi and the functional enhancement of beneficial fungi have been the major topics investigated by researchers. Non-thermal plasma (NTP) is a potential tool to inactivate pathogenic and food-spoiling fungi and functionally enhance beneficial fungi. In this review, we summarize and discuss research performed over the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 207 publications
(235 reference statements)
0
15
0
1
Order By: Relevance
“…However, plasma applications for promoting the production of industrially useful microbial enzymes have rarely been studied. Although previous studies have been conducted using plasma as a mutagenesis tool to generate fungal mutants with a high yield of enzymes or materials, the effects on the cellular process of enzyme production have rarely been explored (see [ 11 ]). Our study provides a series of experimental evidence showing that plasma can be a useful tool for promoting fungal enzyme production by elevating the level of enzyme gene expression and protein secretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, plasma applications for promoting the production of industrially useful microbial enzymes have rarely been studied. Although previous studies have been conducted using plasma as a mutagenesis tool to generate fungal mutants with a high yield of enzymes or materials, the effects on the cellular process of enzyme production have rarely been explored (see [ 11 ]). Our study provides a series of experimental evidence showing that plasma can be a useful tool for promoting fungal enzyme production by elevating the level of enzyme gene expression and protein secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, non-thermal atmospheric pressure plasma has been applied to improve the yield of fungal secreted enzymes [ 11 ]. Plasma is considered as the 4th state of matter [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionized gases, such reactive oxygen, nitrogen, charged species, and electrons, are produced from ambient air or specific gases at an atmospheric or lower than atmospheric pressure through the application of high voltage electric current and radiation in range of the UV, visible, and infrared region [68][69][70]. Radiofrequency power, microwave power, direct current, or alternating current are used for plasma discharge using different techniques such as direct barrier discharge, corona discharge, and plasma jet [70,71]. NTP is an effective method against many spores and is popular in the pharmaceutical, food industry, and agriculture.…”
Section: Non-thermal Plasma (Ntp)mentioning
confidence: 99%
“…Julak et al [72] observed the inactivation of Alternaria sp., Aspergillus oryzae using corona discharge plasma (9 KV, 300 µA, filtered air) and Byssochlamys nivea, Cladosporium sphaerospermum using dielectric barrier discharge plasma (high voltage, air) within 10 to 40 min of application. Veerana et al [70] reviewed the application of the plasma method in detail for the inactivation of many fungal spores such as A. niger and Penicillium citrinum using dielectric barrier discharge plasma (3 kV at 230 Hz), C. albicans using linear micro discharge plasma jet, Fusarium oxysporum using Dielectric barrier discharge plasma (0.75 KV, 80 mA, air), etc.…”
Section: Non-thermal Plasma (Ntp)mentioning
confidence: 99%